2016
DOI: 10.9734/bmrj/2016/23191
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Urinary Tract Infection among Pregnant Women Receiving Antenatal Care in Two Primary Health Care Centres in Karu Nasarawa State, Nigeria

Abstract: Aim: To determine the prevalence of urinary tract infections among pregnant women receving antenatal care in two primary health care centres in Karu Nasarawa State. Place and Duration of Study: This study was carried out in two primary health care centres in Karu Nasarawa State between March-August, 2015. Methodology: A total of 150 pregnant women were enrolled for this study. Mid stream urine sample was collected from each pregnant woman, analysed and cultured on cystein lactose electrolyte deficient (CLED) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…The findings of the study reveal that the UTI prevalence is 80.0% and this rate of prevalence is higher than in previous studies which accounts for [4.2% (Bigwan and Elijah, 2013), 11% (Ibeneme et al, 2011), 17.19% (Akram et al, 2007), 22% (Ekweozor and Onyemenen, 1996), 29.3% (Ochada et al, 2014), 35.5% (Ebie et al, 2001), 38.6% (Akinyemi et al, 1997), 47% (Ojo et al, 2004), 48% (Agbagwa et al, 2015)] in Nigeria; [34.5% (Dash et al, 2013), 36.68% (Mehta et al, 2013), 10.86% (Kothari and Sagar, 2008), 40.4% (Yengkokpam et al, 2007)] in India; [49% in Trinidad and Tobago (Orrett, 2001)]; and [14.6% (Uddin et al, 2016)] in Bangladesh. However, higher prevalence rate of UTI as seen in this study has been reported by various authors in Nigeria 62.67% (Ajide et al, 2016), Cameroon 59.8% (Nzalie et al, 2016), India (Prakash and Saxena, 2013) and Mexico (Garc´ıa-Mor´ua et al, 2009) which showed such more highly significant uropathogens of 53.82% and 97.3% respectively. The regional disparities in prevalence rate supports earlier report made by Amin et al (2009), that the relationships and variances in the type and distribution of uropathogens may result from different environmental (geographical) conditions and host factors, practices such as health care and education programmes, It is worthwhile to remark that our patients were from an insurgence raveled region (Northeastern, Nigeria), and most of them are displaced from their localities, thus warranting them conceding their hygiene practices such as hand washing and bathing habits, because access to water becomes very challenging, subsequently exposing them to this worrisome prevalence rate.…”
Section: Discussioncontrasting
confidence: 43%
“…The findings of the study reveal that the UTI prevalence is 80.0% and this rate of prevalence is higher than in previous studies which accounts for [4.2% (Bigwan and Elijah, 2013), 11% (Ibeneme et al, 2011), 17.19% (Akram et al, 2007), 22% (Ekweozor and Onyemenen, 1996), 29.3% (Ochada et al, 2014), 35.5% (Ebie et al, 2001), 38.6% (Akinyemi et al, 1997), 47% (Ojo et al, 2004), 48% (Agbagwa et al, 2015)] in Nigeria; [34.5% (Dash et al, 2013), 36.68% (Mehta et al, 2013), 10.86% (Kothari and Sagar, 2008), 40.4% (Yengkokpam et al, 2007)] in India; [49% in Trinidad and Tobago (Orrett, 2001)]; and [14.6% (Uddin et al, 2016)] in Bangladesh. However, higher prevalence rate of UTI as seen in this study has been reported by various authors in Nigeria 62.67% (Ajide et al, 2016), Cameroon 59.8% (Nzalie et al, 2016), India (Prakash and Saxena, 2013) and Mexico (Garc´ıa-Mor´ua et al, 2009) which showed such more highly significant uropathogens of 53.82% and 97.3% respectively. The regional disparities in prevalence rate supports earlier report made by Amin et al (2009), that the relationships and variances in the type and distribution of uropathogens may result from different environmental (geographical) conditions and host factors, practices such as health care and education programmes, It is worthwhile to remark that our patients were from an insurgence raveled region (Northeastern, Nigeria), and most of them are displaced from their localities, thus warranting them conceding their hygiene practices such as hand washing and bathing habits, because access to water becomes very challenging, subsequently exposing them to this worrisome prevalence rate.…”
Section: Discussioncontrasting
confidence: 43%
“…Regarding the age, our results were similar to other studies (Nascimento et al, 2012;Lawani et al, 2015;Younis et al, 2019) which identified that mainly young adults between 20 and 29 years were affected. However, different results were found by Bukola et al, (2016) which found prevalence of pregnant women over 35 years.…”
Section: Resultsmentioning
confidence: 82%
“…However, other studies have shown different findings. Studies conducted by Lawani et al (2015) and Bukola et al (2016) showed that pregnant women in the third trimester were more infected. Furthermore, Pagnonceli et al (2010) related the highest incidence of urinary tract infection in the 3rd gestational trimester, which is a more worrying reality because, due to the fact that the pregnant woman does not feel manifestations that indicate UTI, and this problem can go unnoticed and cause serious complications.…”
Section: Resultsmentioning
confidence: 99%
“…The overall prevalence of UTI in this study is high and of great concern. Pregnancy is one the factors that predispose to UTI due to ureteral dilation, urinary stasis (abnormalities in the structure of urinary outflow tract that may result in incomplete emptying of the bladder), reduced immune function, and presence of vesicoureteric reflex (backward flow of urine from bladder into the kidney) and difficulty with hygiene due to a distended pregnant belly (Onoh et al, 2013;Ajide et al, 2016). It has also been reported that up to 70% of pregnant women develop glycosuria, which encourages bacteria growth in urine (Alemu et al, 2012;Getachew et al, 2012).…”
Section: Journal Of Biology and Life Sciencementioning
confidence: 99%
“…Pregnancy enhances the progression from asymptomatic to symptomatic bacteriuria which could lead to other adverse obstetric outcomes such as prematurity, low-birth weight and higher fetal mortality rates (Getachew et al, 2012). In Nigeria, the prevalence of UTI among antenatal patients has been reported in Benin, Ebonyi and Nassarawa State as 13.8%, 55% and 62.67% respectively (Alfred et al, 2013;Onuoha and Fatokun, 2014;Ajide et al, 2016).…”
Section: Introductionmentioning
confidence: 99%